Simulated front crawl swimming performance related to critical speed and critical power - Toussaint, H. M; Wakayoshi, K.; Hollander, A. P.; Ogita, F. (Medicine & Science in Sports & Exercise, 1998)
Using a sensitivity analysis, it was demonstrated that the critical velocity is indicative for the capacity of the aerobic energy system. Estimates of the anaerobic swimming capacity, however, were influenced by variations in both anaerobic and aerobic energy release. Therefore, it was concluded that the anaerobic swimming capacity does not provide a reliable estimate of the anaerobic capacity.